2002
DOI: 10.1002/tera.10040
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effects of folate deficiency on embryonic development through the establishment of a folate deficient mouse model

Abstract: Female mice fed a folic acid deficient diet and 1% succinyl sulfathiazole exhibited many of the characteristics common to human folic acid deficiency, including decreased plasma and RBC folate, increased plasma homocysteine, and poor reproductive outcomes. Thus, an excellent model has been created to investigate the mechanism(s) underlying the origin of birth defects related to folic acid deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
112
4
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(127 citation statements)
references
References 49 publications
10
112
4
1
Order By: Relevance
“…Maternal periconceptional supplementation with pteroylmonoglutamic acid (the synthetic form of folic acid) significantly decreases the risk of neural tube defects in offspring, and recent studies have suggested that it may also protect the embryo against the development of congenital heart defects (CHD) [1][2][3][4]. Risk for these defects may also be modified by polymorphisms in genes encoding enzymes in the folate metabolic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal periconceptional supplementation with pteroylmonoglutamic acid (the synthetic form of folic acid) significantly decreases the risk of neural tube defects in offspring, and recent studies have suggested that it may also protect the embryo against the development of congenital heart defects (CHD) [1][2][3][4]. Risk for these defects may also be modified by polymorphisms in genes encoding enzymes in the folate metabolic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The BA1 mesenchyme is populated with neural crest cells (NCCs) derived from the margins of the developing neural tube. Like the neural tube, NCCs appear to be particularly sensitive to maternal dietary and plasma folate concentrations during development (17,47,48) and methyl donor supplementation supports the role of folate in 1-carbon metabolism. This may partially explain how the NCC-populated BA1 mesenchyme could be a suitable target for methyl donor action.…”
Section: Discussionmentioning
confidence: 89%
“…Burgoon and co-authors on IRC mice for a duration of 4 weeks on 0% folic acid diet, revealed a reduction in male reproduction (less offspring per litter), in response to a folate deficient diet and therefore provided a further support to the human data (Burgoon et al, 2002). …”
Section: Folate Deficiency In Rodentsmentioning
confidence: 83%